Production and Therapeutic Use of a Factor XI Concentrate from Plasma - Bolton-Maggs, P H B; Wensley, R T; Kernoff, P B A; Kasper, C K; Winkelman, L; Lane, R S; Smith, J K (Thrombosis and Haemostasis, 1992)
Factor XI deficiency is an uncommon bleeding disorder usually manifested by excessive bleeding after surgery or trauma. Until recently the only effective therapy has been fresh-frozen plasma (FFP) infusion. We describe the efficacy and safety of a new factor XI concentrate produced from human donor plasma by a modification of the method used for antithrombin III concentrate. The mean recovery of factor XI in the circulation measured on 62 occasions was approximately 91% of the injected dose, and the mean half-disappearance-time was 52 h. The concentrate was used for 31 invasive procedures in 30 patients, including 16 patients who had a definite bleeding tendency on previous occasions, with normal haemostasis being achieved in all but 1. Only 1 patient (previously experiencing allergy to FFP) experienced adverse effects during infusion. Monitoring of liver function tests and viral antibody status in suitable patients has shown no evidence of transmission of hepatitis viruses, HIV-1 or parvovirus B19.We conclude that this concentrate provides effective treatment for patients with factor XI deficiency. Preliminary results suggest safety from virus transmission, but this needs to be established in further studies of previously untreated patients.